Effect of Different Disinfectants on Staphylococcus aureus and Candida albicans Transferred to Alginate and Polyvinylsiloxane Impression Materials - Fereydoun Parnia; Ali Hafezeqoran; Elnaz Moslehifard; Farhang Mahboub; Mohammadreza Nahaei; Mohammad Akbari Dibavar (Tabriz University of Medical Sciences, 2009)
Background and aims. Several products have been marketed for disinfecting impression materials. The present study evaluated the effect of Deconex, Micro 10, Alprocid and Unisepta Plus sprays on Staphylococcus aureus and Candida albicans transferred to alginate and polyvinylsiloxane impression materials. Materials and methods. A total of 180 impressions of a maxillary model (90 alginate and 90 polyvinylsiloxane impressions) were taken for the purpose of this in vitro study. Half of the impressions were infected with Staphylococcus aureus and the other half were infected with Candida albicans. Then the microorganisms were cultured and their counts were determined. Subsequently, the impressions were divided into groups of 15 impressions each. Each group was disinfected with Deconex, Micro10, Alprocid and Unisepta Plus according to manufacturers' instructions except for the control group. The culturing procedure was repeated after disinfection and microbial counts were determined again. Data was analyzed by ANOVA and paired-sample t-test. Results. There were statistically significant differences in the means of S. aureus and C. albicans counts before and after the use of disinfectants (P < 0.05). The use of the four disinfectants reduced S. aureus counts to zero in 80% of the cases. There were no statistically significant differences in S. aureus count reductions between the four disinfectants evaluated (P = 0.31). Micro 10 was more effective on alginate; Deconex was more efficient for polyvinylsiloxane and Alprocid had a better efficacy in both impression materials in eliminating C. albicans (P < 0.05). Conclusion. All the disinfectants evaluated have high disinfecting postentials.